2021
DOI: 10.1055/s-0041-1735904
|View full text |Cite
|
Sign up to set email alerts
|

Management of Coincident Pituitary Macroadenoma and Cavernous Carotid Aneurysm: A Systematic Literature Review

Abstract: Introduction Pituitary adenomas are a common intracranial pathology with an incidence of 15 to 20% in the population while cerebral aneurysms are less common with a prevalence of 1:50 patients. The incidence of aneurysms in patients with pituitary adenoma has been estimated at 2.3 to 5.4% of patients; however, this remains unclear. Equally, the management of concomitant lesions lacks significant understanding. Methods A case report is presented of a concomitant cerebral aneurysm and pituitary adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 12 In these procedures, antiplatelet therapy is generally not required and this intervention has been shown to provide aneurysm protection with low morbidity and facilitate transsphenoidal resection of the adenoma. 6 For these reason, the treatment of the coexistence pathology can be performed within the same procedure (in this study is reported in 19.35% of cases). In cases of direct clipping, 12 the surgical approach and the timing become problems (it was performed just in 11 cases reported).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“… 12 In these procedures, antiplatelet therapy is generally not required and this intervention has been shown to provide aneurysm protection with low morbidity and facilitate transsphenoidal resection of the adenoma. 6 For these reason, the treatment of the coexistence pathology can be performed within the same procedure (in this study is reported in 19.35% of cases). In cases of direct clipping, 12 the surgical approach and the timing become problems (it was performed just in 11 cases reported).…”
Section: Discussionmentioning
confidence: 85%
“…The clinical symptoms are mainly caused by hormones secreted by PAs or by compression on the surrounding brain tissues and optic nerve, while for associated IA, the diagnosis is often incidental (51/94, 54.26%). 3 It seems that older age 9 and cavernous sinus invasion increase the rate of coexistence 6 ; some studies 9 have also hypothesized that female sex may be a risk factor for AIs in patients with pituitary tumors, but the reported data do not suggest this difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations